Evolutionary Developments in Plant Specialized Metabolism, Exemplified by Two Transferase Families - Kusano, Hiroaki; Li, Hao; Minami, Hiroshi; Kato, Yoshihiro; Tabata, Homare; Yazaki, Kazufumi (Frontiers in Plant Science, 2019)
Plant specialized metabolism emerged from the land colonization by ancient plants, becoming diversified along with plant evolution. To date, more than one million metabolites have been predicted to exist in the plant kingdom, and their metabolic processes have been revealed on the molecular level. Previous studies have reported that rates of evolution are greater for genes involved in plant specialized metabolism than in primary metabolism. This perspective introduces topics on the enigmatic molecular evolution of some plant specialized metabolic processes. Two transferase families, BAHD acyltransferases and aromatic prenyltransferases, which are involved in the biosynthesis of paclitaxel and meroterpenes, respectively, have shown apparent expansion. The latter family has been shown involved in the biosynthesis of a variety of aromatic substances, including prenylated coumarins in citrus plants and shikonin in Lithospermum erythrorhizon. These genes have evolved in the development of each special subfamily within the plant lineage. The broadness of substrate specificity and the exon-intron structure of their genes may provide hints to explain the evolutionary process underlying chemodiversity in plants.